PKCθ Regulates T Cell Motility via Ezrin-Radixin-Moesin Localization to the Uropod - Cannon, Judy L. (Public Library of Science, 2013)
Cell motility is a fundamental process crucial for function in many cell types, including T cells. T cell motility is critical for T cell-mediated immune responses, including initiation, activation, and effector function. While many extracellular receptors and cytoskeletal regulators have been shown to control T cell migration, relatively few signaling mediators have been identified that can modulate T cell motility. In this study, we find a previously unknown role for PKCθ in regulating T cell migration to lymph nodes. PKCθ localizes to the migrating T cell uropod and regulates localization of the MTOC, CD43 and ERM proteins to the uropod. Furthermore, PKCθ-deficient T cells are less responsive to chemokine induced migration and are defective in migration to lymph nodes. Our results reveal a novel role for PKCθ in regulating T cell migration and demonstrate that PKCθ signals downstream of CCR7 to regulate protein localization and uropod formation.